Leveraging dissemination and implementation science to facilitate adoption of a human nutrition research e-learning course - Denise Daudelin; Penny M. Kris-Etherton; Alyssa Cabrera; Anna L. Thompson; Kris M. Markman; Linfei Chen; Alice H. Lichtenstein (Journal of Clinical and Translational Science)
Abstract